RELATIONSHIP BETWEEN LAW AND SOCIAL JUSTICE VALUES OF PANCASILA FOR THE LIFE OF INDONESIAN SOCIETY - Hafaz Muhammad Bintang; Kahfi Sukri Bayuandri; Shiren Safitri (LEX SOCIETAS: Journal of Law and Public Administration, 2024)
Indonesia is a country of law based on Pancasila. With the problems that continue to arise in Indonesian society, Pancasila will be a source of reference for forming and enforcing law in Indonesia. If justice does not exist, law will only be a formality. The rights and obligations of citizens are no longer protected by law. As a result, Pancasila becomes a philosophy of life and a guide for the life of the nation and state. They must be used as a guideline for acting, behaving, and making policies in the Indonesian system of government. This study uses a qualitative approach. This study will show that, given the large number of people in Indonesia who want justice, law is tied to Pancasila. Every life must have values ​​of justice, because in essence something that is unfair will cause inequality, therefore the presence of law can help realize true justice. The relationship between law and the social justice values of Pancasila is fundamental in shaping the legal framework and social fabric of Indonesia. Pancasila, as the foundational ideology of the state, incorporates principles of justice, equality, and social welfare that directly influence the formulation and application of laws and policies. This paper explores how the social justice values enshrined in Pancasila, such as fairness and equal opportunity, are integrated into the Indonesian legal system and their impact on society. It analyzes the challenges and opportunities in ensuring that Pancasila’s values are reflected in everyday legal practices, including judicial decisions and governmental actions. Despite the legal framework in place, gaps remain in the effective implementation of these ideals, particularly in addressing social disparities and ensuring access to justice for all. This study suggests that while significant progress has been made, continued efforts are needed to align the legal system more closely with the ideals of Pancasila, ensuring that social justice becomes a lived reality for every citizen in Indonesia